Intertextuality in media texts of genre of interview with politics. Article 1 - Shulinova, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article deals with modern interviews with Ukrainian politicians from the point of view of the existence of precedent intertexts and their functions. Intertextuality induces the recipient to thinking activity: to determine the existence of an intertextual text, to identify it, to understand the newly created meaning, to evaluate it, to perceive / not to perceive, that is, to compare with the values’ scale and possible intellectual compromise with the world’s reflection and the pragmatic purpose of the author. The basic groups of precedent phenomena are defined: precedent texts and precedent situations, which are analyzed in more detail, precedent names, precedent statements. The main sources of precedent texts in interviews with politicians are legislative documents that are logical from the point of view and the thematic specifics of texts and communicative strategies in the media representatives of the political community. In the analyzed interviews precedent scenarios are presented through direct nominations and indirectly through the description of phenomena, facts, details that are associated for most respondents with a particular situation, with a certain emotional / evaluative attitude that the communicants support or attempt through comments, refinements, refutation, ridiculing, etc. change to the opposite, ie to form strategically defined beliefs.